Asked by Harshita Bhola | 8th Mar, 2011, 03:17: PM

Expert Answer:

Dear Student,

Following is the solution to your question

Assume the series as a, a+d, a+2d, a+3d, a+4d,........

where S1  = a; S2 = 2a+d and S3 = 3a+3d

the given expression for d will be

d = S3 – k*S2 + S1

d= 3a + 3d – k*(2a+d) + a

k*(2a+d) = 4a +2d

k*(2a+d) = 2*(2a +d)

k = 2

Team Topperlearning

Answered by  | 9th Mar, 2011, 10:29: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.